2012
DOI: 10.1111/j.1464-410x.2012.11609.x
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative morbidity and mortality related to radical cystectomy: a multi‐institutional retrospective study in Japan

Abstract: What ' s known on the subject? and What does the study add?Radical cystectomy remains associated with comparatively high perioperative morbidity and mortality, despite improvements in surgical techniques and perioperative care. At present, most studies on the complications associated with open radical cystectomy were derived from Western academic high-volume centres, and data from Japan and other Asian countries were very limited.Using the modifi ed Clavien grading system and 11 category grouping reported from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 31 publications
(53 reference statements)
6
54
1
2
Order By: Relevance
“…Moreover, it is our opinion that measuring 90-day mortality is more relevant than 30-day mortality since improvements in postoperative care may postpone surgery-related deaths beyond 30 days. 16 Supporting this point, Shabsigh and colleagues found that 45% of RC-related deaths occurred between 30 and 90 days and would not have been reported in the traditional 30-day time period. 4 Our mortality rates at 30, 60 and 90 days were 2.8%, 5.3% and 7.5%, respectively; these rates are considered high when compared with recent literature and reports from around the world.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, it is our opinion that measuring 90-day mortality is more relevant than 30-day mortality since improvements in postoperative care may postpone surgery-related deaths beyond 30 days. 16 Supporting this point, Shabsigh and colleagues found that 45% of RC-related deaths occurred between 30 and 90 days and would not have been reported in the traditional 30-day time period. 4 Our mortality rates at 30, 60 and 90 days were 2.8%, 5.3% and 7.5%, respectively; these rates are considered high when compared with recent literature and reports from around the world.…”
Section: Discussionmentioning
confidence: 72%
“…One reason for the lower use of RC for elderly patients might be that RC frequently causes complications. Takada et al [11] evaluated [12] reported an overall incidence of complications of 64 % and an incidence of major complications of 13 %. In our study the overall incidence of complications was 34.3 % and the incidence of severe complications was 16.5 % (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Regarding the continence rate, they observed 45% complete continence (daytime and night-time), and 36% daytime continence only. Because "daytime continence only" probably means daytime continence + night-time incontinence, approximately 80% of patients would have "daytime continence," being consistent with previous observations.…”
Section: 3mentioning
confidence: 97%
“…2,3 Furthermore, they reported a low early complication rate of 22.6% compared with previous studies, although they did not provide the details of postoperative management. 4,5 Regarding the continence rate, they observed 45% complete continence (daytime and night-time), and 36% daytime continence only. Because "daytime continence only" probably means daytime continence + night-time incontinence, approximately 80% of patients would have "daytime continence," being consistent with previous observations.…”
Section: Editorial Comment Editorial Comment To Use Of Sigmoid Colon mentioning
confidence: 97%